2009
DOI: 10.1002/chem.200900369
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐Assisted Self‐Assembly of Pyrene Foldamers

Abstract: The self-organization of oligopyrene foldamers is described. Bi- and tri-segmental oligomers composed of nucleotides and non-nucleosidic, achiral pyrene monomers form double-stranded helical structures, as shown by absorbance, fluorescence, and CD spectroscopy. The mixed nature of alternating aromatic and phosphate groups ensures water solubility which, in turn, favors folding of the aromatic units. Pyrene molecules also assemble though interstrand stacking interactions. Structural organization of the pyrene u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 82 publications
2
48
1
Order By: Relevance
“…Their arrangement can be described as a displaced, face-to-face stacking interaction. The proximity of the two pyrenes is in agreement with the observed excimer fluorescence in solutions of DNA hybrids containing 1,8-linked, non-nucleosidic pyrenes in opposite positions (41,61,69). However, the orientation of the two aromatic planes is not parallel, as might be expected, but wedged (25–30°).…”
Section: Resultssupporting
confidence: 86%
“…Their arrangement can be described as a displaced, face-to-face stacking interaction. The proximity of the two pyrenes is in agreement with the observed excimer fluorescence in solutions of DNA hybrids containing 1,8-linked, non-nucleosidic pyrenes in opposite positions (41,61,69). However, the orientation of the two aromatic planes is not parallel, as might be expected, but wedged (25–30°).…”
Section: Resultssupporting
confidence: 86%
“…Specific colorimetric and ratiometric fluorescence responses toward trivalent metals have been exhibited by pyridinyl-functionalized tetraphenylethene [2]. Moreover, only a few reports of AIE behavior were demonstrated by excimer formations of fluorophores containing pyrene rings [32][33][34][35][36][37][38][39][40][41]. Surprisingly, present results of our pyrene-based fluorophore with Schiff-base probes showed another special aggregation induced ratiometric emission (AIRE) processes upon increasing water content.…”
Section: Introductioncontrasting
confidence: 60%
“…Recently, we reported that oligoarenotides (oligomers with an alternating phosphodiester-aromatic hydrocarbon motif) exhibit similar structural properties as nucleic acids, and although the aromatic hydrocarbons cannot engage in any sort of Watson–Crick related hydrogen bonding, the individual strands interact via an interstrand stacking motif [4548]. Herein we describe a series of DNA-based hybrids (Fig.…”
Section: Introductionmentioning
confidence: 99%